PSYCHOLOGICAL ADAPTATION OF FOOTBALL REFEREES TO THE VAR SYSTEM - Gevorgyan , A. E. (Modern Psychology, 2019)
The article presents an analysis of the positive and negative aspects of refereeing from the psychological point of view of an arbitrator for a new football refereeing system (VAR-video assistant). As well as a comparison of the quantitative and qualitative errors of the arbitrators who judged at the last two world championships (2014 and 2018).